Ethics Responsibility: Using Social Media of Social Work Practice in Thailand - Khangpiboon, Kath; Nimtaluong , Panrat; Jundai, Ronnarong (Indonesian Social Work Consortium (ISWC), 2023)
This study aims to develop communication guidelines for social workers using social media. Thematic analysis of documents and reviews was used as the research methodology. The importance of understanding the use of social media in social work practice and the need for guidelines to ensure professional ethics are upheld. The guidelines incorporate legal knowledge and standards, including relevant laws such as the Kingdom of Thailand 2017 Constitution and the Social Work Profession Act 2013. Emphasise the importance of digital literacy, technology literacy, and ethical communication skills to communicate with clients and multidisciplinary teams effectively. The Thailand Council of Social Work Professions has presented guidelines for public communication for social work professionals. The guidelines stress the importance of social workers considering the best interests of their clients when providing online services. e-professionalism is also essential for social workers to explore ethical considerations in the digital world.